2020
DOI: 10.1021/acsomega.0c03985
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Driven Photoelectrocatalytic Water Splitting Using Z-Scheme Ag-Decorated MoS2/RGO/NiWO4 Heterostructure

Abstract: Herein, we have successfully constructed a solid-state Z-scheme photosystem with enhanced light absorption capacity by combining the optoelectrical properties of AgNPs with those of the MoS 2 /RGO/NiWO 4 (Ag-MRGON) heterostructure. The Ag-MRGON Zscheme system demonstrates improved photo-electrochemical (PEC) water-splitting performance in terms of applied bias photon-to-current conversion efficiency (ABPE), which is 0.52%, and 17.3-and 4.3-times better than those of pristine MoS 2 and MoS 2 /NiWO 4 photoanodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…It is worth mentioning that photogenerated electrons transported from g-C 3 N 4 and originally excited electrons on Ag particles are impacted by surface plasma resonance. Ag particles have a limited capacity for catalytic hydrogen creation, as previously mentioned; therefore, SPR supplied to H + is not sufficient in the absence of e – from g-C 3 N 4 . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that photogenerated electrons transported from g-C 3 N 4 and originally excited electrons on Ag particles are impacted by surface plasma resonance. Ag particles have a limited capacity for catalytic hydrogen creation, as previously mentioned; therefore, SPR supplied to H + is not sufficient in the absence of e – from g-C 3 N 4 . …”
Section: Resultsmentioning
confidence: 99%
“…As a result of its excellent thermal and chemical stability as well as its appropriate band energy, g-C 3 N 4 is an appealing material for photocatalysis. The electronic conductivity, surface area, and remarkable adsorption capabilities of g-C 3 N 4 are all enhanced by the addition of carbon nanomaterials, like r-GO. Combining g-C 3 N 4 with r-GO enhanced the visible-light responsiveness, lengthened the lifetime of the photogenerated charge carriers, enhanced the adsorption properties, and raised the specific surface area. The employment of physical and chemical interactions to integrate different building blocks in the development of these heterostructured photocatalysts is a particularly versatile approach. All of these heterostructures now have new opportunities for scientific study and technological use in photocatalysis, owing to the newly developed 2D/2D or three-dimensional (3D)/2D heterojunctions, which have exceptional qualities, such as their clear “face to face” connection with a great interface space and solid interactions, the wide range of light responsiveness enclosed by many 2D materials with varying bandwidth, the improved interfacial charge separation, and other factors. …”
Section: Introductionmentioning
confidence: 99%
“…A solid-state Ag NP-decorated MoS 2 /reduced graphene oxide (RGO)/NiWO 4 Z-scheme photosystem was constructed. 179 In addition to the Z-scheme function, the RGO mediator and the plasmonic effect of Ag NPs facilitate the charge transfer to enhance photocatalytic efficiency. Nagajyothi et al 180 reported a ZnFe 2 O 4 / MoS 2 Z-scheme heterostructure achieved an H 2 production rate of 142.1 mmol h À1 g À1 , which is 2.3 times higher than that of pristine MoS 2 .…”
Section: Tmd-based Heterostructuresmentioning
confidence: 99%
“…The improvement of photoelectrodes is of course important to enhance the overall performance. Lower band gap materials and/or heterostructures may offer improved solar performance by utilising more visible light, with extensive investigations primarily focused on solar energy harvesting rather than water treatment [11].…”
Section: Nanomaterials For Photoelectrocatalysismentioning
confidence: 99%